PERSEPSI MASYARAKAT TERHADAP KEBERADAAN HUTAN KEMASYARAKATAN DESA WOMBO KALONGGO - Nurhaya, Nurhaya; Wahid, Abdul; Maiwa, Arman (Universitas Tadulako, 2020)
Management stakeholders include the Lore lindu National Park Center, Sedoa village communities around Lore lindu National Park, and the management of a tambing lake, Forest Police (Polhut), Farmer groups (Gapoktan), Village Government, Customary leaders and local NGOs (walhi) . Stakeholders' interests in the management of the National Park consist of interests to preserve the area, and interests to benefit from the existence of the National Park such as the utilization of Tambing Lake tourism. While the presence of these stakeholders can have a positive and negative influence on the preservation of the Lore lindu National Park area. Stakeholders who can be involved in resolving issues related to the desire to expand plantations in the Lore lindu National Park consist of the Balai Besar Lore lindu National Park, Sedoa villagers around the Lore lindu National Park, and the management of the tambing lake, Forest Police (Polhut), Farmer groups (Gapoktan), village government, traditional leaders and local NGOs (walhi). While the roles that can be done to overcome this problem can be in the form of control functions, physical assistance (plant seedlings), technical assistance (land management techniques, counseling, training and assistance), as well as support for the management of Lore lindu National Park management. Keywords: Stakeholder Mapping In Managing TNLL, Sedoa Village